Assessment of the Relationship between Ulcerative Colitis and Forkhead Box P3 Polymorphisms - Ülger, Yakup; Akgöllü, Ersin (Turkish Journal of Gastroenterology, 2021)
Background/Aims: Ulcerative colitis (UC) is a chronic disease that does not have a definitive treatment and causes repetitive inflammation of the colon and impaired quality of life. The FOXP3 gene codes FOXP3 protein responsible for development and function of regulatory T (Treg) cells. The rs2232365 A/G and the rs3761548 A/C polymorphisms of FOXP3 gene were indicated to be associated with inflammation-related diseases such as ulcerative colitis. The effectiveness of Treg cells, which act as immune-suppressors in the control of inflammation, can be affected by these polymorphisms. The aim of the present study was to evaluate the association between these polymorphisms with ulcerative colitis.Materials and Methods: The current study researched the FOXP3 gene polymorphisms in 146 patients with UC and in 292 healthy individuals by a real-time polymerase chain reaction (RT-PCR).Results: The patients with rs2232365 G allele had a 1.44-fold higher UC risk than patients carrying other allele (P=0.013), and had significantly a 2.56-fold higher risk for extent of UC (P=0.001). Contrary, rs3761548 polymorphism didn't reach statistically significant in any analysis.Conclusion: This is the first study to reveal the relationship of the rs2232365 and the rs3761548 polymorphisms with ulcerative colitis in Caucasian population. The rs2232365 has an important effect on the risk of UC. The current study suggests that these polymorphisms should be explored together with the FOXP3 expression and FOXP3+ Treg cell count in blood and colon tissue of UC patients to clarify the exact effect of FOXP3 polymorphisms on UC risk.